Difference in Uptake of Tetrodotoxin and Saxitoxins into Liver Tissue Slices among Pufferfish, Boxfish and Porcupinefish - Yuji Nagashima; Akira Ohta; Xianzhe Yin; Shoichiro Ishizaki; Takuya Matsumoto; Hiroyuki Doi; Toshiaki Ishibashi (Marine Drugs, 2018)
Although pufferfish of the family Tetraodontidae contain high levels of tetrodotoxin (TTX) mainly in the liver, some species of pufferfish, boxfish of the family Ostraciidae, and porcupinefish of the family Diodontidae do not. To clarify the mechanisms, uptake of TTX and saxitoxins (STXs) into liver tissue slices of pufferfish, boxfish and porcupinefish was examined. Liver tissue slices of the pufferfish (toxic species Takifugu rubripes and non-toxic species Lagocephalus spadiceus, L. cheesemanii and Sphoeroides pachygaster) incubated with 50 µM TTX accumulated TTX (0.99–1.55 µg TTX/mg protein) after 8 h, regardless of the toxicity of the species. In contrast, in liver tissue slices of boxfish (Ostracion immaculatus) and porcupinefish (Diodon holocanthus, D. liturosus, D. hystrix and Chilomycterus reticulatus), TTX content did not increase with incubation time, and was about 0.1 µg TTX/mg protein. When liver tissue slices were incubated with 50 µM STXs for 8 h, the STXs content was <0.1 µg STXs/mg protein, irrespective of the fish species. These findings indicate that, like the toxic species of pufferfish T. rubripes, non-toxic species such as L. spadiceus, L. cheesemanii and S. pachygaster, potentially take up TTX into the liver, while non-toxic boxfish and porcupinefish do not take up either TTX or STXs.